An examination of the acquired preparedness model among college student marijuana users. Issue 7 (3rd October 2022) - Berey, Benjamin L.; Frohe, Tessa M.; Pritschmann, Ricarda K.; Yurasek, Ali M.
Abstract: Objective To examine the Acquired Preparedness Model using a behavioral impulsivity facet and positive marijuana expectancies to examine direct and indirect effects on marijuana use and related problems. Participants : 250 college students (61.7% female, 54% white) recruited from a southeastern university. Methods : Participants completed an online survey of delay reward discounting, marijuana expectancies, consideration of future consequences, and marijuana-related outcomes. Results : Delay reward discounting and consideration of future consequences related to marijuana-related problems, but not marijuana use. However, positive marijuana expectancies did not mediate the relation between impulsivity and marijuana outcomes. Conclusions : These results emphasize delay reward discounting and consideration of future consequences as important factors associated with marijuana-related problems. Interventions aimed at decreasing delay reward discounting and augmenting future orientation may be effective in college students who report light to moderate marijuana use. Future studies would benefit from longitudinal study designs using multiple impulsivity measures among light and heavy users.